Epithelial and stromal remodelling following femtosecond laser–assisted stromal lenticule addition keratoplasty (SLAK) for keratoconus - Mario Nubile (Nature Portfolio, 2021)
Abstract The purpose of this study was to evaluate corneal epithelium and stromal remodelling with anterior segment optical coherence tomography in patients who have undergone stromal lenticule addition keratoplasty (SLAK) for advanced keratoconus. This was a prospective non-comparative observational study. Fifteen eyes of 15 patients with advanced keratoconus underwent implantation with a cadaveric, donor negative meniscus-shaped intrastromal lenticule, produced with a femtosecond laser, into a stromal pocket dissected in the recipient cornea at a depth of 120 μm. Simulated keratometry, central corneal thickness (CTT), corneal thinnest point (CTP), central epithelial thickness (CET), central and peripheral lenticule thickness, anterior and posterior stromal thickness were measured. Regional central corneal epithelial thickness (CET) and variations in the inner annular area (IAT) and outer annular area (OAT) were also analysed. All parameters were measured preoperatively and 1, 3, and 6 months postoperatively. The average anterior Sim-k decreased from 59.63 ± 7.58 preoperatively to 57.19 ± 6.33 D 6 months postoperatively. CCT, CTP, CET, and OAT increased and IAT decreased significantly after 1 month. All parameters appeared unchanged at 6-months except that of OAT that further increased. Lenticule thickness was stable. In conclusion we observed that SLAK reshapes the cornea by central flattening with stromal thickening and epithelial thickness restoration.